Professional Acquisition of M. bovis in Calabria Region (Southern Italy): A Challenging Case of Osteomyelitis in a Migrant Patient from Bulgaria - Angela Quirino; Carlo Torti; Alessio Strazzulla; Salvatore Nisticò; Luisa Galati; Giorgio Settimo Barreca; Angelo Giuseppe Lamberti; Giuseppina Berardelli; Maria Pacciarini; Giorgio Gasparini; Vincenzo Pisani; Antonio Gambardella; et al. (Case Reports in Infectious Diseases)
We report herein the first case of a coinfection with Brucella spp., M. bovis, and Enterobacter cloacae in a butcher who moved from Bulgaria to Italy. Molecular typing suggested professional acquisition of M. bovis in Italy. So, surveillance and preventive measures need to be implemented.